Rapid evaluation method for performance of artificial graphite raw material
By conducting polarized microstructure analysis and comprehensive structural data calculation on artificial graphite raw materials, an association curve is established to quickly predict the capacity of finished products after graphitization, solving the problem of low raw material evaluation efficiency in the existing technology, and achieving efficient and accurate raw material performance evaluate.
Patent Information
- Application Number
- CN202311052384.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-21
AI Technical Summary
The prior art is difficult to quickly and effectively evaluate the electrochemical properties of artificial graphite raw materials, resulting in low efficiency in raw material selection and product design, and it takes 3-4 months to obtain finished product capacity data during graphitization.
By conducting quantitative analysis of polarized microstructures on artificial graphite raw materials, comprehensive structural data are calculated based on contribution factors of different microstructures, and correlation curves are established to quickly evaluate the electrochemical properties of raw materials and predict the capacity of the finished product after graphitization.
It greatly shortens the raw material evaluation cycle, saves manpower and material resources, improves production efficiency, and has high accuracy. The prediction results are similar to the actual finished product capacity after graphitization.
Smart Images

Figure BDA0004404877880000052 
Figure BDA0004404877880000091 
Figure BDA0004404877880000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial graphite raw material evaluation, and relates to a method for quickly evaluating the performance of artificial graphite raw materials. Background Art
[0002] It has become an industry consensus that the global new energy vehicle market has entered the fast lane of development. In the next 3 to 5 years, the new energy vehicle industry will grow rapidly, and it is expected that the global new energy vehicle production will exceed 10 million in 2025. Lithium-ion batteries have the advantages of high energy density, long cycle life, good charge and discharge performance, high operating voltage, no memory effect, less pollution and high safety. At the same time, compared with various types of fuel cells, air batteries and supercapacitor batteries, lithium-ion battery technology is obviously more mature.
[0003] At present, the negative electrode materials of lithium batteries are generally divided into carbon-based negative electrodes and non-carbon-based negative electrodes. Among them, carbon-based negative electrodes can be divided into graphite, hard carbon, soft carbon negative electrodes, etc. Graphite can be divided into artificial graphite, natural graphite, and intermediate phase carbon microspheres; non-carbon-based negative electrodes include lithium titanate, tin alloy negative electrodes, silicon negative electrodes, etc. In 2021, the shipment volume of China's lithium battery negative electrode market was 720,000 tons, a year-on-year increase of 97%, of which artificial graphite accounted for 84% and natural graphite accounted for 14%. The reason why artificial graphite has become the main lithium storage material is that artificial graphite has a rich source of raw materials, has a layered structure suitable for lithium ion embedding and de-embedding, can form lithium-graphite interlayer compounds, and has the advantages of low voltage platform and small volume change during embedding and de-embedding.
[0004] There are three ways to store lithium in graphite materials: interlayer lithium storage, end face lithium storage and surface lithium storage. The more developed the graphite layer is, the more lithium is inserted, and the greater the lithium storage capacity is. The carbon atoms exposed at the edge of the graphite sheet are in an amorphous state, with high energy, and are active sites for lithium ions, that is, end face lithium storage. The bonding between carbon atoms on the surface of graphite and lithium ions is similar to that of the edge, that is, surface lithium storage. However, when the voltage is lower than 0.25V, most lithium ions begin to embed into the layer and form graphite interlayer compounds of different orders, that is, interlayer lithium storage contributes more than 93% of the capacity. Generally, soft carbon (such as asphalt coke, petroleum coke, etc.) must be graphitized before it can be converted into a graphite structure. Therefore, graphitization is one of the most critical processes in the preparation of negative electrodes using soft carbon as raw materials. This process accounts for 50% of the cost of graphite negative electrodes and is also the most expensive part of graphite negative electrodes. The main graphitization furnaces are Acheson resistance furnaces (crucible or box type), internal series furnaces and continuous furnaces. The graphitization process cycle usually takes 40 days (loading the furnace, heating up, cooling down, and unloading the furnace).
[0005] At present, the intrinsic relationship between heat treatment temperature and material graphite microcrystal parameters has been systematically studied. For example, Chinese patent document CN111766173A discloses that the raw coke sample is dried, roughly broken and fully sieved to 4 mm to obtain primary coke powder, which is then heat treated at 700-800°C in a nitrogen atmosphere and then crushed to fully sieve 0.071 mm to obtain secondary coke powder; the secondary coke powder is vacuum dried at 110-140°C, and then heated from 50°C to 900°C in an air atmosphere at a rate of 2-5°C / min for thermogravimetric testing to determine the reaction starting temperature of the change in graphitization degree and the reaction starting temperature of the reversible capacity change.
[0006] Chinese patent document CN107764681A discloses taking at least two groups of coke raw materials, making the particle size D50 deviation between the groups of coke raw materials ≤2μm, and the specific surface area deviation within each group of coke raw materials ≤2m 2 / g, volatile matter deviation ≤2%; conduct thermogravimetric test on each coke raw material sample in at least 2 groups of coke raw materials in an oxidizing atmosphere to obtain the starting temperature of weight loss of oxidation reaction; use the graphitized products of the coke raw material samples as negative electrode active materials to make pole pieces, and test the capacity of the finished products after graphitization of the coke raw materials; finally, draw a graph based on the data of the starting temperature of weight loss of oxidation reaction and the capacity of the finished products after graphitization of the coke raw materials, and obtain the relationship between the capacity of the finished products after graphitization of the coke raw materials and the starting temperature of weight loss of oxidation reaction.
[0007] The above are all thermogravimetric analyses of soft carbon coke samples, which reflect the thermal stability of fixed carbon. It is a relatively macroscopic property manifestation and cannot distinguish differences such as crystal growth or disappearance caused by differences in microcrystalline structure. The correlation between capacity and temperature points is also low. However, the correlation between the microcrystalline structure of soft carbon and the microcrystalline parameters after graphitization has not yet been established. Therefore, if you want to know the electrochemical properties of the negative electrode material finally made from soft carbon raw materials, it must be graphitized, then assembled into a battery and tested for electrochemical performance; it takes at least 3-4 months from obtaining the raw materials to the electrochemical data.
[0008] In view of the orderly arrangement of graphite microcrystals in the radial / axial direction, the disappearance of grain boundaries, the formation of CC six rings at the crystal interface, and the growth of crystals during the graphitization process, it also involves the catalytic reaction of unsaturated carbon atoms at the boundaries of graphite layers, the thermal shock of carbon atoms or gas molecules, the anisotropic properties of graphite microcrystals, the van der Waals forces between graphite layers and other microscopic thermodynamic or kinetic behaviors. All of the above are related to the microcrystalline structure of the raw materials. Therefore, if the correlation between the electrochemical properties of the graphitized material can be established based on the microstructural characteristics of the raw materials, the capacity performance data of the finished artificial graphite can be predicted more quickly and conveniently.
[0009] However, there will be a complex correspondence between the direct use of soft carbon for structural analysis and the subsequent electrochemical correlation. This is because most petroleum coke, asphalt coke, and needle coke are prepared by delayed coking process, and the thermal reaction of the coke sample in the upper part of the reactor is not thorough. Especially for petroleum coke products, a large amount of unreacted heavy aromatic components remain in the coke during the production process, the degree of coking reaction is uneven, and the structure of some carbon microcrystals is unstable. In the usual artificial graphite processing process, the structure will be transformed or eliminated during the carbonization and graphitization process. Therefore, it is necessary to quickly heat treat or modify the soft carbon structure to make the retained structure more representative and the data more accurate. Summary of the invention
[0010] In view of this, the present invention provides a rapid evaluation method for the performance of artificial graphite raw materials, which is used to guide the raw material selection and product design of lithium battery negative electrode materials. The evaluation method uses the polarized microstructure quantitative analysis data of the artificial graphite raw materials, and combines the contribution factors of different microstructures to calculate the comprehensive structure data to quickly evaluate the electrochemical performance of the artificial graphite raw materials and predict the capacity of the finished product after graphitization, solving the problem of low efficiency caused by the current traditional negative electrode industry that it takes 3-4 months to obtain the capacity of the finished product of the artificial graphite raw materials after graphitization, greatly shortening the evaluation cycle, saving manpower and material resources, and improving production efficiency.
[0011] To achieve the above object, the present invention provides the following technical solutions:
[0012] A method for quickly evaluating the performance of artificial graphite raw materials comprises the following steps:
[0013] Crushing: drying and crushing the soft carbon material to 0.071-1 mm to obtain the crushed soft carbon material;
[0014] Heat treatment: heat treating the crushed soft carbon material in a nitrogen atmosphere containing water vapor to obtain a heat-treated soft carbon material;
[0015] Microstructure test: 4-5g of the heat-treated soft carbon material is placed in a stationary state with a metallographic sample preparation epoxy resin and a curing agent for curing and polishing, and the obtained optical film is tested by a polarizing microscope to obtain the content of each optical structure;
[0016] Capacity test: The soft carbon material is dried, preliminarily crushed and classified to obtain soft carbon powder, which is then carbonized, graphitized, crushed and classified to obtain graphite powder; the graphite powder is subjected to battery assembly and charge and discharge tests to obtain the capacity of the finished battery after graphitization of the soft carbon material;
[0017] Constructing a correlation curve: correlating the content of each optical tissue with the capacity of the finished battery to obtain a correlation curve;
[0018] Evaluation: evaluating the finished product capacity of the soft carbon material to be evaluated by the correlation curve (i.e., predicting the finished product battery capacity of the soft carbon material to be tested by testing the content of each optical structure in the soft carbon material to be tested and combining the correlation curve);
[0019] Wherein, in the process of constructing the correlation curve, the soft carbon materials used in the capacity testing step and the crushing step are the same, and at least 10 kinds;
[0020] When the soft carbon material to be tested is evaluated using the correlation curve, the capacity testing step and the correlation curve construction step are omitted.
[0021] Optionally, in the pulverizing step of the method for rapid evaluation of the properties of artificial graphite raw materials provided by the present invention, the moisture content of the soft carbon material after drying is less than 0.1%, and the true density is 1.362-1.425 g / cm 3 , volatile matter is 3% to 20%, ash content is 0.01% to 0.5%, and S content is 0.1% to 5%;
[0022] The soft carbon material is selected from at least one of petroleum coke, needle coke and pitch coke;
[0023] The soft carbon materials are at least 16 kinds.
[0024] Optionally, in the heat treatment step of the method for rapid evaluation of the performance of artificial graphite raw materials provided by the present invention, the temperature of the heat treatment is 1100-1300°C, the time is 0.5-2h; the volume content of water vapor in the nitrogen atmosphere containing water vapor is 8%-12%. The specific heat treatment device can be a tubular furnace or a furnace body of any shape with controllable atmosphere, as long as the device is equipped with a steam generating device and can adjust the flow rate. Specifically, the heat treatment step can be carried out as follows:
[0025] The crushed soft carbon material is placed in the device, and then nitrogen is introduced into the device, and water vapor is introduced on the basis of nitrogen, and the flow rate of water vapor is controlled to 8% to 12% of the nitrogen volume flow rate, and then heated from room temperature to 1100 to 1300°C at a rate of 60 to 80°C / min in a nitrogen atmosphere containing water vapor. The nitrogen flow rate is set according to the volume in the furnace (90 to 120 ml nitrogen / L furnace volume).
[0026] Optionally, in the microstructure testing step of the method for rapid evaluation of the performance of the artificial graphite raw material provided by the present invention, the content of each optical structure is calculated according to the following formula:
[0027] Wherein, the total number of effective points of each optical tissue is at least 500;
[0028] In the microstructure testing step, the classification of each optical structure in the carbon material is shown in the following table:
[0029] Table 1
[0030]
[0031] A1, A2, A3, A4, A5, A6, A7 and A8 are used to measure the contents of small inlay, medium inlay, coarse inlay, small piece, large piece, short thin fiber, coarse fiber and long fiber respectively, and the unit is %; in the above Table 1, a1, a2, a3, a4, a5, a6, a7 and a8 represent the structural contribution factor of each optical organization, that is, the contribution rate of different optical organization structures to the capacity of the finished battery, so as to accurately express the capacity relationship between soft carbon materials with different structures and artificial graphite.
[0032] Optionally, in the method for rapid evaluation of the performance of the above-mentioned artificial graphite raw material provided by the present invention, in the microstructure test step, the crushed soft carbon material, epoxy resin and curing agent are placed in a mold for curing for 24 hours to form a focal light sheet, and then the focal light sheet is polished to obtain a light sheet with a flat surface, no pits and scratches; and the light sheet is placed under a polarizing microscope for analysis, and the moving ruler step length is adjusted to ensure that more than 500 effective measurement points are evenly distributed throughout the sheet. Starting from one end of the sample, the optical tissue of the substance under the cross intersection is verified. The content of each optical tissue is expressed as the percentage of its statistical points to the effective points. Among them, the mold used for curing, as well as the types of epoxy resin and curing agent are not specifically limited, and conventional ones in the industry that can cure soft carbon materials with epoxy resin and curing agent are sufficient. The specific crushing steps and the process of preparing optical slices in the microstructure testing steps can refer to the provisions of 6.1, 6.2 and 6.3 in YB / T077-2017. The specific method of testing using a polarizing microscope can refer to YBT 4822-2020.
[0033] Optionally, in the capacity test step of the method for rapid evaluation of the performance of the artificial graphite raw material provided by the present invention, the primary crushing can be performed by jaw crushing or hammer crushing, and after graphitization, the crushing is performed by a mechanical crusher, a jet mill or a ball mill;
[0034] The D50 of the soft carbon powder is 15-18 μm; the D10 of the soft carbon powder is 3-4 μm, and the D90 is 25-27 μm; the particle size deviation of different samples does not exceed ±2 μm. A larger particle size difference will cause a particle size effect, resulting in data deviation.
[0035] The parameters of carbonization and graphitization in the graphitization process are not specifically limited, and conventional parameters in the industry may be used. For example, the following carbonization and graphitization parameters may be used:
[0036] The carbonization temperature is 700-1500°C, the time is 0.5-3h, and the heating rate is 1-10°C / min; preferably, the carbonization temperature is 800-1200°C, the time is 1-2h, and the heating rate is 3-4°C / min;
[0037] The graphitization temperature is 2800-3100°C, and the time is 1-20h; preferably, the graphitization temperature is 2950-3050°C, and the time is 5-10h; however, once the heating program and final temperature and time of carbonization and graphitization are selected, they need to be consistent among samples, with a deviation of no more than ±5°C and a time of no more than ±5min.
[0038] The graphite powder has a D50 of 14-16 um and a specific surface area of less than 2 cm 3 / g, the content of magnetic substances is less than 1ppm; too high specific surface area may be caused by improper operation of the graphitization process, unreasonable temperature control, or the material is not fully cooled before contact with air and other reasons, which need to be strictly maintained consistent.
[0039] The battery assembly and charge-discharge test method is not specifically limited, and conventional methods in the industry may be used. For example, a battery assembly and charge-discharge test method including the following steps may be used:
[0040] The graphitized product of each soft carbon material is used as the negative electrode active material, and the mixture is mixed and slurried according to the mass ratio of graphite: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR = 95:1.5:1.5:2, and then coated on copper foil and dried to obtain a surface density of 70g / m 2 , compacted density is 1.75g / cm 3 The pole piece;
[0041] The pole piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent composed of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1, and a charge and discharge test is performed; preferably, the voltage range of the charge and discharge test is 0.001~2.5V, and the first delithiation capacity obtained is the capacity of the finished battery after the soft carbon material is graphitized.
[0042] Optionally, in the step of constructing a correlation curve in the method for rapid evaluation of the performance of the artificial graphite raw material provided by the present invention, the step further includes calculating the content of each optical structure in combination with the structural contribution factor of the optical structure to obtain a comprehensive structural parameter X, and then correlating the comprehensive structural parameter X with the finished battery capacity;
[0043] The comprehensive structural parameter X is calculated according to the following formula:
[0044] X=(a1×A1+a2×A2+a3×A3+a4×A4+a5×A5+a6×A6+a7×A7+a8×A8) / 100;
[0045] The correlation curve is Y=βX+γ, that is, Y=β(1×A1+2×A2+5×A3+10×A4+90×A5+20×A6+50×A7+100×A8) / 100+γ; wherein Y is the capacity of the finished battery, γ is the intercept, and β is the slope.
[0046] Optionally, in the method for rapid evaluation of the performance of artificial graphite raw materials provided by the present invention, after calibration, the correlation curve is Y=0.6035X+327.54, and the unit of Y is mAh / g.
[0047] The rapid evaluation method for the performance of the artificial graphite raw material provided by the present invention is to obtain the content A1 to A8 of each optical structure by crushing the soft carbon material to be tested according to the above-mentioned pulverization and microstructure test steps, and then calculate the comprehensive structural parameter X, and substitute the comprehensive structural parameter X into the correlation curve to obtain the predicted battery capacity of the finished product after graphitization of the corresponding soft carbon material to be tested. It should be noted that when evaluating the soft carbon material to be tested, the predicted finished product battery capacity result is based on the capacity test method when constructing the correlation curve (that is, the predicted finished product battery capacity is the same capacity test method as when constructing the correlation curve).
[0048] Compared with the prior art, the present invention has the following advantages:
[0049] 1. The method for rapid evaluation of the performance of artificial graphite raw materials provided by the present invention is applicable to soft carbon raw materials such as ordinary petroleum coke and needle coke. The microstructure of the samples after crushing and heat treatment is quantitatively analyzed, and the comprehensive structural data is calculated in combination with the contribution factors of different microstructures. At the same time, the soft carbon raw materials are graphitized to obtain graphite powder for battery assembly, and the capacity of the finished battery is tested. Finally, the calculated comprehensive structural data is associated with the capacity of the finished battery to predict the capacity performance of the graphitized product corresponding to the soft carbon raw material, so as to achieve the purpose of rapid evaluation of artificial graphite raw materials. The method is simple and fast, has high accuracy, saves time and effort, and is highly efficient.
[0050] 2. Compared with the existing methods, the rapid evaluation method for the performance of artificial graphite raw materials provided by the present invention is based on microstructural analysis, by processing and modifying the structure in an atmosphere containing water vapor, and the research is based on the stable microcrystalline structure retained after the treatment, and is correlated with the electrochemical properties tested after graphitization, thereby solving the problem in the existing methods that the relationship between some soft carbon structures and electrochemical properties is complex and does not have a linear relationship. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The present invention provides a calibration diagram of comprehensive structural parameters obtained by quantitatively analyzing the microstructure of a soft carbon raw material and the capacity of the prepared artificial graphite. DETAILED DESCRIPTION
[0052] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0053] Example 1
[0054] This embodiment provides a method for quickly evaluating the performance of artificial graphite raw materials, comprising the following steps:
[0055] Crushing: 10 different soft carbon materials were selected, dried to a moisture content of less than 0.1%, crushed to about 1 mm with a jaw crusher, and then passed through 200-mesh and 16-mesh molecular sieves in turn to obtain crushed soft carbon materials with a particle size range of 0.071 to 1 mm; the specific properties of various soft carbon materials after drying are shown in Table 2 below.
[0056] Heat treatment: Place the crushed soft carbon material in a tubular furnace, introduce nitrogen and then introduce water vapor on the basis of nitrogen, control the flow rate of water vapor to 10% of the nitrogen volume flow rate, and then heat from room temperature to 1200°C at a rate of 70°C / min in a nitrogen atmosphere containing water vapor, and carry out heat treatment for 1 hour.
[0057] Microstructure test: Weigh 4.5g of the above-mentioned soft carbon material after heat treatment, put it in the bottom of the mold, and then pour the mixture of epoxy resin (CER1000 for metallographic sample preparation) and curing agent (CEH500) mixed in a mass ratio of 2:1 into the mold containing the crushed soft carbon material to 3 / 4, and let it stand at room temperature for 24 hours to cure. After the sample is cured, use an automatic grinder and polisher to grind it with sandpaper from coarse to fine, and then polish it with alumina polishing liquid until the optical film is mirror-like, and the surface is flat, without pits and scratches; rinse it with clean water and observe it under a polarizing microscope, select appropriate parameters to collect polarized photos, and obtain 520 valid photos. Starting from one end of the sample, verify what kind of optical organization the material under the cross point belongs to. The content of each optical organization is expressed as the percentage of its statistical points to the valid points, and the content of each optical organization is calculated specifically according to the following formula:
[0058]
[0059] The microstructures of the 10 kinds of crushed soft carbon materials were tested using the above method. The test results of the contents of various optical structures in the various soft carbon materials are shown in Table 3 below.
[0060] Capacity test: The soft carbon material is dried, jaw crushed and air flow milled to obtain soft carbon powder, then heated to 1100°C at a rate of 4°C / min and maintained at this temperature for 2 hours for carbonization, and then graphitized at 3000°C for 10 hours. After graphitization, it is crushed and classified to obtain graphite powder with a magnetic material content of less than 1ppm; the properties of the soft carbon powder and graphite powder obtained from various soft carbon materials are shown in Table 2 below.
[0061] The graphite powder was used as the negative electrode active material. The graphite powder: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR were mixed in a mass ratio of 95:1.5:1.5:2 to prepare a slurry. The slurry was then coated on a copper foil and dried to obtain a surface density of 70 g / m 2 , compacted density is 1.75g / cm 3 a pole piece; taking the pole piece as the working electrode, the lithium sheet as the counter electrode, 1 mol / L LiPF6 as the electrolyte, the solvent in the electrolyte being a mixed solvent of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1, a charge and discharge test is performed; the specific charge and discharge test voltage range is 0.001V~2.5V, and the first delithiation capacity obtained is the finished battery capacity after graphitization of the soft carbon material.
[0062] The microstructures of the 10 soft carbon materials were tested using the above method, and the 10 soft carbon materials were the same as the 10 soft carbon materials in the crushing step. The specific test results are shown in Table 3 below.
[0063] Table 2
[0064]
[0065]
[0066] Table 3
[0067]
[0068] Constructing a correlation curve: The content of each optical tissue obtained in the above microstructure test step is combined with the structural contribution factor of each corresponding optical tissue to obtain a comprehensive structural parameter X,
[0069] X=(a1×A1+a2×A2+a3×A3+a4×A4+a5×A5+a6×A6+a7×A7+a8×A8) / 100;
[0070] Then substitute X and the finished capacity battery of each soft carbon material into the correlation curve Y = βX + γ, 336 = β(a1×50+a2×10+a3×5+a4×15+a5×5+a6×10+a7×3+a8×2) / 100+γ338 = β(a1×45+a2×7+a3×8+a4×10+a5×6+a6×9+a7×10+a8×5) / 100+γ341 = β (a1×42+a2×8+a3×10+a4×10+a5×8+a6×6+a7×11+a8×5) / 100+γ345=β(a1×34+a2×5+a3×10+ a4×7+a5×20+a6×6+a7×11+a8×7) / 100+γ350=β(a1×25+a2×8+a3×13+a4×7+a5×15+a6×5+a7× 14+a8×13) / 100+γ354=β(a1×20+a2×7+a3×15+a4×5+a5×18+a6×6+a7×14+a8×15) / 100+γ35 7=β(a1×17+a2×5+a3×20+a4×5+a5×15+a6×5+a7×15+a8×18) / 100+γ360=β(a1×10+a2×4+a3× 18+a4×9+a5×18+a6×6+a7×16+a8×19) / 100+γ362=β(a1×8+a2×5+a3×15+a4×6+a5×22+a6×4 +a7×12+a8×28) / 100+γ365=β(a1×5+a2×4+a3×10+a4×8+a5×24+a6×7+a7×12+a8×30) / 100+γ
[0071] After solving the equation and calibrating, we can get: a1 = 1, a2 = 2, a3 = 5, a4 = 10, a5 = 95, a6 = 20, a7 = 50, a8 = 100, β = 0.6035, γ = 327.54;
[0072] Therefore, the calculation formula of the comprehensive structural parameter X is:
[0073] X=(1×A1+2×A2+5×A3+10×A4+95×A5+20×A6+50×A7+100×A8) / 100;
[0074] The calculation formula for the finished battery capacity is:
[0075] Y = 0.6035 (1 × A1 + 2 × A2 + 5 × A3 + 10 × A4 + 95 × A5 + 20 × A6 + 50 × A7 + 100 × A8) / 100 + 327.54, that is, Y = 0.6035X + 327.54. Figure 1 shown.
[0076] evaluate:
[0077] After the petroleum coke A to be tested was dried to a moisture content of less than 0.1%, its true density was tested to be 1.3751 g / cm 3 , volatile matter is 20%, ash content is 0.15%, S content is 0.3%; then it is crushed to about 1mm using a jaw crusher, and then passed through 200 mesh and 16 mesh sieves in turn to obtain petroleum coke A with a particle size range of 0.071 to 1mm.
[0078] The crushed petroleum coke A is placed in a tubular furnace, nitrogen is introduced into the tubular furnace, and water vapor is introduced on the basis of the nitrogen, while the flow rate of water vapor is controlled to be 10% of the nitrogen volume flow rate, and then heated from room temperature to 1200°C at a rate of 70°C / min in a nitrogen atmosphere containing water vapor, and heat treated for 1 hour to obtain heat-treated petroleum coke A.
[0079] Weigh 4.5g of the above-mentioned heat-treated petroleum coke A and put it into the bottom of the mold. Pour the metallographic epoxy resin and curing agent mixed in a mass ratio of 2:1 into the mold containing the crushed soft carbon material to 3 / 4, and let it stand at room temperature for 24 hours to cure. After the sample is cured, use an automatic grinder and polisher to grind it with sandpaper from coarse to fine, and then polish it with alumina polishing liquid until it is mirror-like, and the surface is flat, without pits and scratches; and rinse it with clean water and observe it under a polarizing microscope, select appropriate parameters to collect polarized photos, and obtain 520 valid photos. Starting from one end of the sample, verify what kind of optical organization the material under the cross intersection belongs to. The content of each optical organization is expressed as the percentage of its statistical points to the valid points, and the content of each optical organization is substituted into the calculation formula of the above-mentioned comprehensive structural parameter X to obtain X, and then X is substituted into the calculation formula of the finished battery capacity to obtain the predicted finished battery capacity of the above-mentioned petroleum coke A. The specific results are shown in Table 4 below.
[0080] Verification Example 1
[0081] The petroleum coke A to be tested was dried, crushed by jaws, finely ground by jet mill and sieved to obtain coke powder with particle size D50 = 19.5 μm, D10 = 5.08 μm, and D90 = 29 μm. The coke powder was then heated to 1100°C at a rate of 4°C / min and maintained at this temperature for 2 hours for carbonization. The coke powder was then graphitized at 3000°C for 10 hours. After graphitization, the coke powder was crushed and graded to obtain coke powder with D50 = 16 μm and specific surface area of 1.59 g / cm 3 , graphite powder with magnetic material content less than 1ppm.
[0082] Capacity measurement: The above graphite powder was used as the negative electrode active material, and the mixture was mixed and slurried according to the mass ratio of graphite powder: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR = 95:1.5:1.5:2, and then coated on copper foil and dried to make a surface density of 70g / m 2 , compaction 1.75g / cm 3 The pole piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC with a volume ratio of 1:1:1. The charge and discharge test is carried out. The specific charge and discharge test voltage range is 0.001V~2.5V. The first lithium removal capacity obtained is the finished battery capacity after graphitization of petroleum coke A. The specific results are shown in Table 4 below.
[0083] Example 2
[0084] After the needle coke B to be tested was dried to a moisture content of less than 0.1%, its true density was tested to be 1.4116 g / cm 3 The volatile matter is 5.62%, the ash content is 0.04%, the S content is 0.27%, and then it is crushed to about 1 mm using a jaw crusher, and then passed through 200 mesh and 16 mesh sieves in turn to obtain needle coke B with a particle size range of 0.071 to 1 mm.
[0085] The crushed needle coke B is placed in a tubular furnace, nitrogen is introduced into the tubular furnace, and water vapor is introduced on the basis of the nitrogen, while the flow rate of water vapor is controlled to be 10% of the nitrogen volume flow rate, and then heated from room temperature to 1200°C at a rate of 70°C / min in a nitrogen atmosphere containing water vapor, and heat treated for 1 hour to obtain heat-treated needle coke B.
[0086] Weigh 4.5g of the heat-treated needle coke B and put it into the bottom of the mold. Pour the metallographic epoxy resin and curing agent mixed in a mass ratio of 2:1 into the mold containing the crushed soft carbon material to 3 / 4, and let it stand at room temperature for 24 hours to cure. After the sample is cured, use an automatic grinder and polisher to grind it with sandpaper from coarse to fine, and then polish it with alumina polishing liquid until it is mirror-like, and the surface is flat, without pits and scratches; rinse it with clean water and observe it under a polarizing microscope, select appropriate parameters to collect polarized photos, and obtain 520 valid photos. Starting from one end of the sample, verify what kind of optical structure the material under the cross point belongs to.
[0087] The content of each optical structure is represented by the percentage of its statistical points to the valid points, and the content of each optical structure is substituted into the calculation formula of the comprehensive structural parameter X obtained in the step of constructing the correlation curve in Example 1, X=(1×A1+2×A2+5×A3+10×A4+95×A5+20×A6+50×A7+100×A8) / 100, to obtain X; then X is substituted into the calculation formula of the finished battery capacity obtained in the step of constructing the correlation curve in Example 1, Y=0.6035X+327.54, to obtain the predicted finished battery capacity of the needle coke B. The specific results are shown in Table 4 below.
[0088] Verification Example 2
[0089] The needle coke B to be tested was dried, crushed by jaws, finely ground by jet mill and sieved to obtain coke powder with particle size D50 = 18 μm, D10 = 4.08 μm, and D90 = 30 μm, then heated to 1100 °C at a rate of 4 °C / min and maintained at this temperature for 2 hours for carbonization, and then graphitized at 3000 °C for 10 hours. After graphitization, it was crushed and graded to obtain coke powder with D50 = 16 μm and specific surface area of 1.89 g / cm 3 , graphite powder with magnetic material content less than 1ppm.
[0090] Capacity measurement: The above graphite powder was used as the negative electrode active material, and the mixture was mixed and slurried according to the mass ratio of graphite powder: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR = 95:1.5:1.5:2, and then coated on copper foil and dried to make a surface density of 70g / m 2 , compaction 1.75g / cm 3 The electrode piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC with a volume ratio of 1:1:1. The charge and discharge test is carried out. The specific charge and discharge test voltage range is 0.001V~2.5V. The first lithium removal capacity obtained is the finished battery capacity after the needle coke B is graphitized. The specific results are shown in Table 4 below.
[0091] Example 3
[0092] After the asphalt coke C to be tested is dried to a moisture content of less than 0.1%, its true density is tested to be 1.39 g / cm 3 The volatile matter is 7.47%, the ash content is 0.11%, the S content is 0.4%, and then it is crushed to about 1 mm using a jaw crusher, and then passed through 200 mesh and 16 mesh sieves in turn to obtain asphalt coke C with a particle size range of 0.071 to 1 mm.
[0093] The crushed asphalt coke C is placed in a tubular furnace, nitrogen is introduced into the tubular furnace, and water vapor is introduced on the basis of the nitrogen, while the flow rate of water vapor is controlled to be 10% of the nitrogen volume flow rate, and then it is heated from room temperature to 1200°C at a rate of 70°C / min in a nitrogen atmosphere containing water vapor, and heat treated for 1 hour to obtain the heat-treated asphalt coke C.
[0094] Weigh 4.5g of the above-mentioned heat-treated pitch coke C and put it into the bottom of the mold. Pour the epoxy resin and curing agent mixed in a mass ratio of 2:1 into the mold containing the crushed soft carbon material to 3 / 4, and let it stand at room temperature for 24 hours to cure. After the sample is cured, use an automatic grinder and polisher to grind it with sandpaper from coarse to fine, and then polish it with alumina polishing liquid until it is mirror-like, and the surface is flat, without pits and scratches; rinse it with clean water and observe it under a polarizing microscope, select appropriate parameters to collect polarized photos, and obtain 520 valid photos. Starting from one end of the sample, verify what kind of optical structure the material under the cross point belongs to.
[0095] The content of each optical tissue is expressed as a percentage of its statistical points to the valid points, and the content of each optical tissue is substituted into the calculation formula of the comprehensive structural parameter X obtained in the step of constructing the correlation curve in Example 1, X=(1×A1+2×A2+5×A3+10×A4+95×A5+20×A6+50×A7+100×A8) / 100, to obtain X; then X is substituted into the calculation formula of the finished battery capacity obtained in the step of constructing the correlation curve in Example 1, Y=0.6035X+327.54, to obtain the predicted finished battery capacity of the above-mentioned asphalt coke C, and the specific results are shown in Table 4 below.
[0096] Verification Example 3
[0097] The asphalt coke C to be tested was dried, crushed by jaws, finely ground by jet mill and sieved to obtain coke powder with particle size D50 = 17 μm, D10 = 6.1 μm, and D90 = 27.5 μm, then heated to 1100 °C at a rate of 4 °C / min and maintained at this temperature for 2 hours for carbonization, and then graphitized at 3000 °C for 10 hours. After graphitization, it was crushed and graded to obtain coke powder with D50 = 15 μm and specific surface area of 1.59 g / cm 3 , graphite powder with magnetic material content less than 1ppm.
[0098] Capacity measurement: The above graphite powder was used as the negative electrode active material, and the mixture was mixed and slurried according to the mass ratio of graphite powder: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR = 95:1.5:1.5:2, and then coated on copper foil and dried to make a surface density of 70g / m 2 , compaction 1.75g / cm 3The pole piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC with a volume ratio of 1:1:1. The charge and discharge test is carried out. The specific charge and discharge test voltage range is 0.001V~2.5V. The first lithium removal capacity obtained is the finished battery capacity after the asphalt coke C is graphitized. The specific results are shown in Table 4 below.
[0099] Table 4
[0100]
[0101] It can be seen from the data in the above table that the contents A1-A8 of the optical structures of the different types of coke in Examples 1-3 tested according to the evaluation method provided by the present invention are brought into the calculation formula of the comprehensive structural parameter X, and then the capacity of the artificial graphite is quickly predicted, which is similar to the capacity result measured by assembling the battery after 3-4 months of graphitization process. This shows that the evaluation method provided by the present invention is accurate and reliable, and the prediction time of the evaluation method provided by the present invention only takes about 2-3 days, which not only greatly saves the manpower and material resources of the negative electrode enterprises in screening raw materials, but also provides a basis for coke production units and scientific research institutes to adjust operating conditions and change test conditions, and has significant economic and social benefits.
[0102] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for quickly evaluating the performance of artificial graphite raw materials, characterized in that: The steps include: Crushing: Dry and crush the soft carbon material to 0.071 ~ 1mm, and the crushed soft carbon material was obtained; Heat treatment: heat treating the crushed soft carbon material in a nitrogen atmosphere containing water vapor to obtain a heat-treated soft carbon material; Microstructure test: the heat-treated soft carbon material is subjected to static curing and polishing with epoxy resin and curing agent, and the obtained optical slice is tested by polarizing microscope to obtain the content of each optical structure; Capacity test: carbonizing and graphitizing the soft carbon material to obtain graphite powder; testing the graphite powder to obtain the capacity of the finished battery after graphitization of the soft carbon material; Constructing a correlation curve: correlating the content of each optical tissue with the capacity of the finished battery to obtain a correlation curve; Evaluation: evaluating the finished battery capacity of the soft carbon material to be tested by the correlation curve; Wherein, in the process of constructing the correlation curve, the soft carbon materials used in the capacity testing step and the crushing step are the same, and at least 10 kinds; When the soft carbon material to be tested is evaluated using the correlation curve, the capacity testing step and the correlation curve construction step are omitted.
2. The rapid evaluation method for the performance of artificial graphite raw materials as claimed in claim 1, characterized in that: In the pulverizing step, the moisture content of the soft carbon material after drying is less than 0.1%, and the true density is 1.362-1.425 g / cm 3 , volatile matter is 3% to 20%, ash content is 0.01% to 0.5%, S content is 0.1% to 5%; and / or The soft carbon material is selected from at least one of petroleum coke, needle coke and pitch coke; and / or The soft carbon materials are at least 16 kinds.
3. The rapid evaluation method for the performance of artificial graphite raw materials as claimed in claim 1, characterized in that: In the heat treatment step, the heat treatment temperature is 1100-1300°C and the time is 0.5-2h; The volume content of water vapor in the nitrogen atmosphere containing water vapor is 8% to 12%.
4. The rapid evaluation method for the performance of artificial graphite raw materials as claimed in claim 1, characterized in that: In the microstructure testing step, the content of each optical tissue is calculated according to the following formula: Wherein, the total number of effective points of each optical tissue is at least 500; and / or In the microstructure test step, the classification of optical tissues is shown in the following table: A1, A2, A3, A4, A5, A6, A7 and A8 are used to calculate the contents of small inlay, medium inlay, coarse inlay, small piece, large piece, short thin fiber, coarse fiber and long fiber respectively; a1, a2, a3, a4, a5, a6, a7 and a8 are the structural contribution factors of each optical tissue.
5. The rapid evaluation method for the performance of artificial graphite raw materials as claimed in claim 4, characterized in that: In the capacity testing step, the D50 of the soft carbon powder is 8-22 μm, preferably 15-18 μm; the D10 of the soft carbon powder is 2-5 μm, preferably 3-4 μm, and the D90 is 25-30 μm, preferably D25-27 μm; and / or The carbonization temperature is 700-1500°C, the time is 0.5-3h, and the heating rate is 1-10°C / min; preferably, the carbonization temperature is 800-1200°C, the time is 1-2h, and the heating rate is 3-4°C / min; and / or The graphitization temperature is 2800-3100°C and the time is 1-20h; preferably, the graphitization temperature is 2950-3050°C and the time is 5-10h; and / or The graphite powder has a D50 of 14-16 um and a specific surface area of less than 2 cm 3 / g, the magnetic material content is less than 1ppm; and / or The battery assembly and charge and discharge test includes the following steps: The graphite powder is used as the negative electrode active material, and the mixture is mixed and slurried according to the mass ratio of graphite: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR = 95:1.5:1.5:2, and then coated on copper foil and dried to obtain a surface density of 70g / m 2 , compacted density is 1.75g / cm 3 The pole piece; The pole piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent composed of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1, and a charge and discharge test is performed; preferably, the voltage range of the charge and discharge test is 0.001~2.5V, and the first delithiation capacity obtained is the capacity of the finished battery after the soft carbon material is graphitized.
6. The method for rapid evaluation of the performance of artificial graphite raw materials according to claim 5, characterized in that: The step of constructing the correlation curve also includes combining the content of each optical tissue with the structural contribution factor of the optical tissue to obtain a comprehensive structural parameter X, and then correlating the comprehensive structural parameter X with the finished battery capacity; The comprehensive structural parameter X is calculated according to the following formula: X=(a1×A1+a2×A2+a3×A3+a4×A4+a5×A5+a6×A6+a7×A7+a8×A8) / 100; The correlation curve is Y=βX+γ, wherein Y is the capacity of the finished battery, γ is the intercept, and β is the slope.
Citation Information
Patent Citations
Method for rapidly evaluating coke raw materials
CN107764681A
Method for evaluating quality of coke for lithium battery negative electrode material
CN111766173A
Method for evaluating graphite and / or graphitized carbon material electrochemical performance
CN101126733A
Composite cathode material for lithium ion power and energy storage battery and preparation method thereof and battery
CN101916857A
Carbon material, method for manufacturing same, and application of same
CN106458603A
Cited By
Rapid evaluation method for performance of negative electrode graphite material
CN121454359A